Short-form creative writing : a writer's guide and anthology - Hummel, H. K. (Heather K.); Lenox, Stephanie (Britain: Bloomsbury Publishing, 2019)
"Short-Form Creative Writing: A Writers' Guide and Anthology is a complete introduction to the art and craft of writing in a variety of short forms. The authors introduce both traditional and innovative approaches to the short form and demonstrate how it possesses structure, logic, and coherence while simultaneously resisting expectations. With discussion questions, writing prompts, flash interviews and glossary of key terms, the book covers: - Prose poetry - Flash and micro fiction - The lyric essay - Short shorts - Micro memoir - Cross-genre/hybrid writing - Nano fiction - Sudden fiction - Drabble - Vignette - Postcard poems/fiction Short-Form Creative Writing also includes an anthology, offering inspiring examples of short-form writing in all of the styles covered by the book, including work by: Charles Baudelaire, Elizabeth Bishop, Jorges Luis Borges, Italo Calvino, Trevor Dodge, Grant Faulkner, Robert Hass, Ilya Kaminsky, Aimee Nezhukumatathil, Philip Levine, Anne Sexton and many others"--
A long history of the short form -- Picture this -- Voice, character, and narrator -- Moving through time and space -- The microcosmic sentence -- How to leap: ah-ha moments and associative logic -- Translucent design -- Beg, borrow, and steal -- Finding the funny -- Misfit pleasures -- Not so fast! strategic revision.
Includes indexes.
Keywords: Short story; Creative writing